[tex]c) \ 4\sqrt{3}-\sqrt{27}-2\sqrt{12} = 4\sqrt{3}-\sqrt{9\cdot3}-2\sqrt{4\cdot3} =4\sqrt{3}-\sqrt{9}\cdot\sqrt{3}-2\cdot\sqrt{4}\cdot\sqrt{3} =\\\\=4\sqrt{3}-3\sqrt{3}-2\cdot2\sqrt{3} = \sqrt{3}-4\sqrt{3} = \boxed{-3\sqrt{3}}[/tex]
[tex]d) \ \sqrt{125}+\sqrt{20}+\sqrt{45} = \sqrt{25\cdot5}+\sqrt{4\cdot5} + \sqrt{9\cdot5} = \sqrt{25}\cdot\sqrt{5} + \sqrt{4}\cdot\sqrt{5}+\sqrt{9}\cdot\sqrt{5}=\\\\=5\sqrt{5}+2\sqrt{5}+3\sqrt{5} = \boxed{10\sqrt{5}}[/tex]
9.
[tex]a = 2\sqrt{3}\\b = 4\sqrt{3}\\\\P = a\cdot b\\\\P = 2\sqrt{3}\cdot4\sqrt{3} = 8\sqrt{3^{2}} = 8\cdot3 = \boxed{24}[/tex]
[tex]Obw = 2(a+b)\\\\Obw=2(2\sqrt{3}+4\sqrt{3}) = 2\cdot6\sqrt{3} =\boxed{12\sqrt{3}}[/tex]